Can trade help with fighting the pandemic? Evidence from imports of Chinese medical products - Bo Xu Laike Yang (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
To contain the COVID-19 pandemic, medical products play an important role around the world. This paper studies the relationship between trade and pandemic control by testing the impact of importing medical products from China on COVID-19 cases and deaths. Using a fixed-effects model, we find that there is a significant negative correlation between imports of medical products from China and COVID-19 cases; for every 1 percent increase in protection equipment imported from China, new COVID-19 cases per day drop by 0.24 percent, and COVID-19-related deaths decrease by 0.13 percent in two weeks. The evidence suggests that trade can play a vital role in fighting the pandemic.
Keywords: F18; F64; H12; 330; COVID-19; medical products; trade; China